2012
DOI: 10.31899/rh1.1008
|View full text |Cite
|
Sign up to set email alerts
|

A review and evaluation of multi-sectoral response services ('one-stop centers') for gender-based violence in Kenya and Zambia

Abstract: The Population Council confronts critical health and development issues-from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work with our partners to deliver solutions that lead to more effective policies, programs, and technologies that improve lives around the world. Established in 1952 and headquartered in New York, the Council is a nongovernmental, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…Evaluation research indicated that programmatic effectiveness as survivors and their caregivers perceived the psychosocial support provided by OSCs to be highly effective (Keesbury 2012). Those interviewed reported that they used OSC care repeatedly, including returning for follow-ups, counseling, and support group meetings.…”
Section: Tertiary Prevention: Crisis Responsementioning
confidence: 93%
See 4 more Smart Citations
“…Evaluation research indicated that programmatic effectiveness as survivors and their caregivers perceived the psychosocial support provided by OSCs to be highly effective (Keesbury 2012). Those interviewed reported that they used OSC care repeatedly, including returning for follow-ups, counseling, and support group meetings.…”
Section: Tertiary Prevention: Crisis Responsementioning
confidence: 93%
“…Integrated legal assistance was also appreciated as a beneficial service. The privacy and confidentiality afforded to survivors were also identified positively in survivor satisfaction reports (Keesbury 2012). In this model, social casework is of particular importance in the immediate and long-term (aftercare) social services.…”
Section: Tertiary Prevention: Crisis Responsementioning
confidence: 96%
See 3 more Smart Citations